2018
DOI: 10.1386/ijcm.11.1.21_1
|View full text |Cite
|
Sign up to set email alerts
|

Singing and spirituality in a South African male voice group

Abstract: Since the mid 1970s, a group of twelve business and professional members of a male singing group have continued singing together in Pretoria, South Africa. These singers were interviewed as part of a project on Spirituality and Well-being: Music in the community. From the interview data, two overarching themes emerged, membership benefits and spiritual connections; these are discussed in this research project. Members" views of benefits related mainly to fulfilment of personal, including musical, needs, althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 51 publications
0
1
0
1
Order By: Relevance
“…Naopak vytváření smyslu je syceno často každodenními jednoduchými činnostmi, propojenými s hodnotami a zakotvenými v sociálních vztazích (Spännäri & Laceulle, 2021), přichází v úžasu z vystavení se majestátní kráse přírody, z úcty, pokory a z okamžiků osobního přesahu (Preston & Shin, 2017) aj. Protože se vyskytují bez ohledu na religiózní zakotvení či kontext, mohou být tyto způsoby existence kultivovány, a to už u dětí na prvním stupni základní školy, všímavostí, tedy vědomým vnímáním reality , meditací uvádějící do hlubokých stavů vědomí , ale také prožíváním vděčnosti a úcty (Büssing, 2021), aktivní uměleckou tvorbou, zejména tou hudební (Joseph et al, 2018).…”
Section: Diskuseunclassified
“…Naopak vytváření smyslu je syceno často každodenními jednoduchými činnostmi, propojenými s hodnotami a zakotvenými v sociálních vztazích (Spännäri & Laceulle, 2021), přichází v úžasu z vystavení se majestátní kráse přírody, z úcty, pokory a z okamžiků osobního přesahu (Preston & Shin, 2017) aj. Protože se vyskytují bez ohledu na religiózní zakotvení či kontext, mohou být tyto způsoby existence kultivovány, a to už u dětí na prvním stupni základní školy, všímavostí, tedy vědomým vnímáním reality , meditací uvádějící do hlubokých stavů vědomí , ale také prožíváním vděčnosti a úcty (Büssing, 2021), aktivní uměleckou tvorbou, zejména tou hudební (Joseph et al, 2018).…”
Section: Diskuseunclassified
“…In the authors’ previous overall study (Joseph et al , 2018), the respondents identified reasons for joining and remaining in the group, which included a love of singing, especially in a group, and the fellowship of like-minded individuals with similar origins and backgrounds. Their shared activity includes learning new pieces, rehearsing for performances and the performances themselves.…”
Section: Literature Reviewmentioning
confidence: 99%